2010
DOI: 10.1007/s00464-010-0998-x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic vacuum sponge therapy for esophageal defects

Abstract: Esophageal anastomotic insufficiency and esophageal wall defects of other causes can be treated successfully with endoscopic vacuum sponge therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 22 publications
0
73
0
3
Order By: Relevance
“…Of interest, we observed that ultrasound-guided percutaneous drainages or endoscopic transluminal drainages [30] have been more commonly employed during recent years, both as a supplement to surgery, and sometimes instead of operative treatment. It has recently been suggested that a number of contemporary non-operative techniques, including clips [31], stents [32,33,34], and vacuum therapies [35,36], be used both as primary treatment for the perforation and as secondary tools when complications occur. These techniques are regarded as feasible and promising; however, the overall clinical experience is limited, and most related publications are case series with very few patients.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, we observed that ultrasound-guided percutaneous drainages or endoscopic transluminal drainages [30] have been more commonly employed during recent years, both as a supplement to surgery, and sometimes instead of operative treatment. It has recently been suggested that a number of contemporary non-operative techniques, including clips [31], stents [32,33,34], and vacuum therapies [35,36], be used both as primary treatment for the perforation and as secondary tools when complications occur. These techniques are regarded as feasible and promising; however, the overall clinical experience is limited, and most related publications are case series with very few patients.…”
Section: Discussionmentioning
confidence: 99%
“…4) E-VAC for the treatment of esophageal perforation has been reported after this successful E-VAC treatment for anastomotic leakage after anterior resection of the rectum. [4][5][6] The key concepts of EVAC treatment on esophageal perforation consist of the sealing of the esophageal perforation to prevent the abscess spreading and continuous internal drainage of septic debris from abscess cavity through the polyurethane spongeheaded nasogastric tube. The polyurethane sponge head could be located in mediastinal abscess cavity, intracavitary, or esophageal lumen with sealing the perforation, intraluminary, depending on the abscess cavity size and shape.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, this facilitates a clean wound base and improves consecutive wound closure. [4][5][6] We inserted the sponge-headed nasogastric tube tip into the anastomotic perforation site under endoscopy. The sponge headed nasogastric tube could occlude the perforation site intraluminary.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique inaugurated by us allows sponge placement under full visualization. An intraluminal therapy variation combines the surgical principle of complete occlusion and sufficient internal drainage [12]. We present the first description of successful endoscopic intraluminal vacuum therapy in the treatment of complete esophageal anastomotic necrosis.…”
Section: Introductionmentioning
confidence: 99%